Insights from Government Officials on Strategies and Practices for Managing the Covid-19 Pandemic: A Qualitative Study - Muhammad Aamer Aslam, Mehvish Murtaza, Rubeena Zakar, Junaid Rashid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The study focuses on the challenges faced by government officials in implementing public health interventions to control the spread of COVID-19 in the Lahore District, Pakistan. Material and Methods: This qualitative study used in-depth interviews to collect data from 45 government officials involved in implementing COVID-19 control measures in Lahore District. Results: The study identified several themes related to the challenges faced by government officials, including contact tracing and coordination, disease management and vaccination, public perception and engagement, international travellers management, and implementation strategies. Strategies implemented to address the challenges posed by the pandemic included the utilization of technology, provision of training to staff, coordination with other organizations, identification of high transmission areas, and targeting specific communities or populations at higher risk of infection. Conclusion: The effective management of the COVID-19 pandemic requires a coordinated and multi-faceted response that incorporates various strategies and practices aimed at controlling the spread of the disease and mitigating its impact on communities. The authors recommend prioritizing clear and consistent communication, community engagement, and capacity building in pandemic management strategies. Keywords: Covid-19 pandemic, government officials, public health interventions, contact tracing, vaccination, public perception, international travellers management